Systematization of mechanisms' activity attack of a singing sound - Gasparyan, Անահիտ Ալեքսանդրի (Սաշայի) (Musical Armenia, 2018)
The issues of singing sound attacks varieties in professional singing are observed in this article. The three kinds of sound attacks and laryngeal interacted mechanisms problems, which legitimacy is caused by the organization of the specific nature of these activities, are highlighted. Article is for a wide range of readers, the beginning vocal pedagogues, for the students who study in musical institutions, chorus masters and specialists who deal with the development of declamatory speech.